2018
DOI: 10.1111/jebm.12290
|View full text |Cite
|
Sign up to set email alerts
|

The BPSC: A prospective study investigating the clinical effect of interventional therapy and the risk factors for bladder cancer and benign prostatic hyperplasia in Chinese population

Abstract: Bladder cancer and benign prostatic hyperplasia have been two very common diseases among the elderly men, especially with the aging of the population in the world. We have designed a study to investigate the clinical effect of interventional therapy for plasmakinetic resection of the prostate and plasmakinetic resection of the bladder, which is called "BPSC" (The bladder cancer and benign prostatic hyperplasia study in Chinese population). The BPSC is not only a specific study, it is made up of many studies. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The study subjects were selected from the Bladder Cancer and Benign Prostatic Hyperplasia Study in Chinese Population (BPSC), which was a prospective study investigating the clinical effect of interventional therapy and the risk factors for bladder cancer and BPH ( Zeng et al, 2018 ). This research was reviewed and approved by the Committee for Ethical Affairs of the Zhongnan Hospital of Wuhan University at Wuhan City, Hubei Province (Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…The study subjects were selected from the Bladder Cancer and Benign Prostatic Hyperplasia Study in Chinese Population (BPSC), which was a prospective study investigating the clinical effect of interventional therapy and the risk factors for bladder cancer and BPH ( Zeng et al, 2018 ). This research was reviewed and approved by the Committee for Ethical Affairs of the Zhongnan Hospital of Wuhan University at Wuhan City, Hubei Province (Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…The study subjects were selected from the Bladder Cancer and Benign Prostatic Hyperplasia Study in Chinese Population (BPSC), which was described previously [2830]. As of January 2018, 771 BPH patients were enrolled in the BPSC database.…”
Section: Methodsmentioning
confidence: 99%
“…BPH alone is rarely a fatal condition but can decrease the quality of life. More and more researchers have indicated that BPH may be a new metabolic disease of aging males (Corona et al, 2014; De Nunzio et al, 2014; Vignozzi et al, 2014; Gacci et al, 2015; Li et al, 2018; Shih et al, 2018; Zeng et al, 2018a,b,c). In addition, BPH is a multifactorial and complex disease and its etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BPH is a multifactorial and complex disease and its etiology remains unclear. Hence, the need to identify the etiology or risk factors of BPH is urgent and our team has proposed a study protocol to identify the risk factors for BPH (Zeng et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%